2021
DOI: 10.3390/ma14195676
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Mitigation of Lithium-Ion Battery Failure—A Review

Abstract: Lithium-ion batteries (LiBs) are seen as a viable option to meet the rising demand for energy storage. To meet this requirement, substantial research is being accomplished in battery materials as well as operational safety. LiBs are delicate and may fail if not handled properly. The failure modes and mechanisms for any system can be derived using different methodologies like failure mode effects analysis (FMEA) and failure mode methods effects analysis (FMMEA). FMMEA is used in this paper as it helps to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 220 publications
0
24
0
Order By: Relevance
“…Then, the polymer separator between the anode and cathode will melt down causing a short circuit between the two electrodes. 122 Ultimately, the layered oxide materials decompose and release a large amount of oxygen. 120 …”
Section: Challenges In Ncm Materialsmentioning
confidence: 99%
“…Then, the polymer separator between the anode and cathode will melt down causing a short circuit between the two electrodes. 122 Ultimately, the layered oxide materials decompose and release a large amount of oxygen. 120 …”
Section: Challenges In Ncm Materialsmentioning
confidence: 99%
“…At battery module level, mission profile-oriented battery thermal management is required to prevent the battery from overheating. The implementation of fire control strategies is also mandatory to meet the certification requirements, these include fire detection devices, extinguishing agents and isolated fire zones for distributed energy storage systems to prevent a fire from spreading [69]. Li-Air batteries are a concept still under research.…”
Section: Batteriesmentioning
confidence: 99%
“…For example, Liu et al , developed a hybrid computational method combined with ab initio molecular dynamics and reactive force fields (ReaxFF) and found that the SEI formation switched from the solvent-derived layer to the salt-derived layer by increasing the electrolyte concentration. Owing to the Li–metal anode expansion/contraction, gas release, and battery encapsulation, the dynamic growth process of SEI is inevitably experienced with complex states of stress, where the stress acts in both the xy -direction and z -direction. , In detail, the average thickness for the lithium metal anode increases to about 3–5.5 μm in a Li||Li symmetric cell cycled at 5 mA/cm 2 and 1 mA h/cm 2 , leading to large stress accumulation . The ensuing interfacial pressure has been proved to generate a dense Li deposition (99.49% electrode density) and significantly affect cell performance, , which is attributed to the fact that the stable SEI effectively inhibits lithium dendrite growth especially for LMBs .…”
Section: Introductionmentioning
confidence: 99%